Design of a low-power asynchronous multiplier - Lim, Khoon Aun. (2008)
This thesis pertains to design and analysis of a 16-bit low-voltage (1.1 V) low-power asynchronous parallel multiplier targeted for a low-power asynchronous digital signal processor.